2019
DOI: 10.21608/ajnsa.2019.3711.1087
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Anti-Müllerian Hormone with Antral Follicle Count and Ovarian Volume in Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women during reproductive age. Women with PCOS show raised Anti-Müllerian hormone (AMH) levels, due to increased number of small antral follicles and granulosa cells, and these may lead to anovulation. Measuring antral follicle count (AFC) and ovarian volume (OV) by ultrasound scanning gives insight to the ovarian function. This study is conducted to investigate the relation between AMH with AFC, OV and different biochemical parameters which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…7 Therefore, OV is still a potential diagnostic tool for detecting PCOS. Several studies have investigated the relationship between OV and PCOS, 8 obesity, 9 insulin resistance, 10 androgen activity, 11,12 metabolic syndrome, 13 and AMH levels 12,14,15 in PCOS patients. Furthermore, to date, while an ovarian volume of >10mL is a part of the Rotterdam criteria for PCOS, several research groups have suggested various cut-off points for OV due to variation in population characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…7 Therefore, OV is still a potential diagnostic tool for detecting PCOS. Several studies have investigated the relationship between OV and PCOS, 8 obesity, 9 insulin resistance, 10 androgen activity, 11,12 metabolic syndrome, 13 and AMH levels 12,14,15 in PCOS patients. Furthermore, to date, while an ovarian volume of >10mL is a part of the Rotterdam criteria for PCOS, several research groups have suggested various cut-off points for OV due to variation in population characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, hirsutism is characterized as mild within scores up to 15, moderate from 16-25, and severe above 25. Biochemical HA was determined at the serum testosterone level >2.5 nmol/L [14]. The selection of the control group was carried out using the ultrasound method.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Subjects who have undergone previous ovarian surgery, received cytotoxic drugs or pelvic irradiation, who undergone 3 months of hormone therapy before the study, or had another endocrinological disorder were excluded. The diagnosis of PCOS was based on two of three Rotterdam criteria: (1) irregular menstrual cycles or OA (≥35 days); (2) HA, clinical (the acne presence of acne, or hirsutism) or biochemical manifestations (increase in the level of at least one circulating ovarian androgen); and (3) polycystic ovaries (PCOs) on ultrasound [14].…”
Section: Diagnostic Methodsmentioning
confidence: 99%